Magnetic and dielectric study of Ni2 FeV3 O11-δ - Guskos, N.; V. Likodimos; Glenis, S.; Typek, J.; Majszczyk, J.; Zolnierkiewicz, G.; Blonska-Tabero, A.; Lin, C.L. (Reviews on Advanced Materials Science, 2007)
The magnetic and dielectric properties of the Ni2 FeV3 O11-6 compound synthesized using different annealing routes have been studied by means of static magnetization, electron paramagnetic resonance and dielectric spectroscopy. The temperature dependence of the magnetic susceptibility has shown marked singularities due to the coexistence of many kinds of magnetic interactions. Dielectric measurements have shown a second order phase transition to the ferroelectric state at about 200K. Dielectric loss measurements have shown an intense peak at the same temperature with activation energy of about 0.42 eV. All investigated compounds of the M-Fe-V-O (M=Ni, Zn, Mg) system have displayed a slight anomaly of the EPR parameters at about 200K. This anomaly is interpreted as arising from the competition between different magnetic subsystems preventing the formation of a long-range magnetic order. © 2007 Advanced Study Center Co. Ltd.
cited By 6